Carne e terra: a relação entre raça, corpo e urbanização na formação do centro de Belo Horizonte - Gabriel da Cruz Nascimento (2024)
The research aims to investigate the processes of socio-spatial exclusion in the emerging Belo Horizonte from the construction of a theoretical prism on the relationship between body and urbanization. Bearing in mind that the body constitutes a dimension of practical life little explored in urban studies, it is understood that the inclusion of this element in the research agenda in the field of knowledge of architecture and urbanism contributes both to the review of epistemological stances and to unveiling new ones facets of socio-spatial exclusion. From the mobilization of instruments from phenomenological philosophy and social sciences, the aim is to construct a research object capable of concatenating body and earth to, from this, propose another reading about the consolidation of places and bodies stigmatized in the consolidation from the city center of Belo Horizonte. Through the confrontation between the mobilized theoretical body and historical documents, the research mobilizes methods of sociological and historiographical investigation towards the processes of stigma formation in the consolidation of the central area - currently delimited by Av. do Contorno, in Belo Horizonte, from hypothesis that the production of urban space results, simultaneously, in the production of determined and violated ways of being.